A Sustainable Vision for Healthcare Organizations, A Strategic Response to Global Challenges - Najjar, Asma Ahmed (2023)
This study aims to explore the global challenges that faced by healthcare organizations and exploring innovated approaches & strategies for designing advanced healthcare business ecosystem while alignment with the United Nations' Sustainable Development Goals as a strategic response. A comprehensive literature review and in-depth case study of Cleveland Clinics & comprehensive survey serve as the foundation for identifying best sustainable and innovated strategies to implementing sustainable business models in healthcare organizations. This research adopts a mixed-methods approach, utilizing qualitative data analysis and quantitative performance indicators to evaluate the feasibility and effectiveness of the proposed strategic response plan. In conclusion, this research finds Healthcare organizations are advised to apply innovated approaches and strategies to build sustainable business ecosystem model, enabling them to adapt to fluctuating demands, optimize patient care, and ultimately contribute to a healthier future for individuals, society, environment and economy in the context of escalating global challenges.